Toward a Better Understanding of Dural Arteriovenous Fistula Angioarchitecture: Superselective Transvenous Embolization of a Sigmoid Common Arterial Collector - Shapiro, M.; Raz, E.; Litao, M.; Becske, T.; Riina, H.; Nelson, P.K. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Our aim was to propose a conceptually new angioarchitectural model of some dural arteriovenous fistulas based on subset analysis of transverse and sigmoid type lesions. The “common collector” notion argues for convergence of multiple smaller caliber arterial vessels on a common arterial collector vessel within the sinus wall. Communication of this single collector (or constellation of terminal collectors) with the sinus proper defines the site of arteriovenous fistula, which can be closed by highly targeted embolization, preserving the sinus and avoiding unnecessary permeation of indirect arterial feeders.MATERIALS AND METHODS: One hundred consecutive dural arteriovenous shunts were examined. Thirty-six transverse/sigmoid fistulas were identified within this group and analyzed for the presence of a common arterial collector as well as other parameters, including demographics, grade, treatment approach, and outcome.RESULTS: A common collector was identified in nearly all Cognard type I lesions (15 fistulas with 14 single collector vessels seen) and progressively less frequently in higher grade fistulas. Identification of the common collector requires careful angiographic analysis, including supraselective and intraprocedural angiographies during treatment, and final embolic material morphology.CONCLUSIONS: Detailed evaluation of imaging studies allows frequent identification of a vascular channel in the sinus wall, which we argue reflects a compound, common arterial channel (rather than a venous collector) with 1 or several discrete fistulous points between this vessel and the sinus proper. Targeted closure of this channel is often feasible, with sinus preservation and avoidance of embolic material penetration into arteries remote from fistula site.dAVFdural arteriovenous fistula